2021
DOI: 10.21203/rs.3.rs-159459/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of CSF1R Inhibitor on Glial Cells Population and Remyelination in The Cuprizone Model

Abstract: Multiple sclerosis is a kind of autoimmune and demyelinating disease and its pathological symptoms include inflammation, myelin loss, astrocytosis, and microgliosis. The colony stimulating factor 1 receptor (CSF1R), as an essential factor for the microglial function, and PLX3397 is its specific inhibitor. In this study, we assessed the effect of different doses of PLX3397 for microglial ablation on glial cells population and remyelination process. Sixty male C57BL/6 mice (8 weeks old) were divided into 6 group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Using two mouse lines carrying distinct mutations in the oligodendrocytic PLP1 gene as a MS model, Groh et al (2019) showed that PLX3397, a potent inhibitor of CSF‐1R, attenuates neuroinflammation by reducing the number of resident microglia and attenuating T‐lymphocyte recruitment in the CNS, which leads to an amelioration of demyelination, axonopathic features and neuronal loss in the retinotectal system. Using chronic CPZ‐induced demyelination in mice, Tahmasebi et al (2019) and Tahmasebi et al (2021) have demonstrated that PLX3397 treatment induces an increase in the rate of myelination and a reduction in the rate of nerve fiber destruction and gap area between myelin layers, accompanied by motor recovery. More recently, using acute CPZ‐induced demyelination, Marzan et al (2021) have demonstrated that microglial depletion by PLX3397 administration greatly abrogates demyelination, OLG loss, and reactive astrocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Using two mouse lines carrying distinct mutations in the oligodendrocytic PLP1 gene as a MS model, Groh et al (2019) showed that PLX3397, a potent inhibitor of CSF‐1R, attenuates neuroinflammation by reducing the number of resident microglia and attenuating T‐lymphocyte recruitment in the CNS, which leads to an amelioration of demyelination, axonopathic features and neuronal loss in the retinotectal system. Using chronic CPZ‐induced demyelination in mice, Tahmasebi et al (2019) and Tahmasebi et al (2021) have demonstrated that PLX3397 treatment induces an increase in the rate of myelination and a reduction in the rate of nerve fiber destruction and gap area between myelin layers, accompanied by motor recovery. More recently, using acute CPZ‐induced demyelination, Marzan et al (2021) have demonstrated that microglial depletion by PLX3397 administration greatly abrogates demyelination, OLG loss, and reactive astrocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis of myelin debris (Cignarella et al, 2020; Ding et al, 2021; Shen et al, 2021) and production of protective factors (Aryanpour et al, 2021) can enhance remyelination, while production of inflammatory mediators can impede remyelination (Thomas & Pasquini, 2018). Microglial ablation using antagonists of the CSF1R show increased remyelination (Tahmasebi et al, 2021); as did astrocyte ablation using La-aminoadipate (Madadi et al, 2019). Reducing Ca 2+ influx into astrocytes has been shown to reduce both astrocyte and microglial activation, as well as promote remyelination (Zamora et al, 2020); suggesting that actions of LKE on voltage gated Ca 2+ channels could contribute to its actions.…”
Section: Discussionmentioning
confidence: 99%